Health Education Influence on Changing WUS Behavior in Early Detection of Breast Cancer - Elizawarda, Elizawarda; Desfauzia, Evi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Data from Global Cancer Statistics in 2018 revealed 18.1 million new cancer cases globally, with Indonesia ranked 8th in Southeast Asia. A study in Mekarsari Delitua village found 4.5% of women suspected of breast cancer, with varying screening rates. A project in Mekarsari Delitua village aimed to educate women on breast cancer prevention through videos. The research was quantitative in nature using a quasi-experimental design (pre test and post test control group). The research sample was 59 comprehensive participants in the intervention group and control group. Data analysis used Wilcoxon.. In 2022, a study in Mekarsari Delitua Village found that counseling sessions improved attitudes and knowledge scores on Breast Cancer Prevention. The mean difference was 22.25, indicating a positive impact. A Breast Cancer Prevention video also increased practicing breast self-examination (SADARI) scores, from 29.88 to 46.80. The statistical analysis showed a substantial enhancement in respondents' prevention practices post-video intervention, indicating a positive impact on the community. Videos have a strong impact on shaping the preventive behavior of women regarding breast cancer. It is recommended that village leaders collaborate with health workers to enhance health education for women of childbearing age. This partnership aims to empower the community in detecting and safeguarding against breast cancer. The study suggests that counseling positively influenced both attitudes and knowledge regarding Breast Cancer Prevention.